Analysis of a membrane reactor: influence of membrane characteristics and operating conditions - Tanna, Nikunj P.; Mayadevi, S. (International Journal of Chemical Reactor Engineering, 2007)
Modeling of an esterification reaction in a batch pervaporation membrane reactor (PVMR), and an analysis of the PVMR performance under different reaction conditions for different membrane characteristics are presented. Esterification of ethyl alcohol with acetic acid was considered as the model reaction. The PVMR performance for this reaction could be represented by a 2-step series model. The PVMR performance was similar to that of the batch reactor when both the reactors were in the kinetic regime. However, the performance of the PVMR was superior to that of the batch reactor when both were in the intermediate/equilibrium regime of the reaction. In these regions, the PVMR performance was influenced/limited by the membrane flux and selectivity. The analysis showed that the membrane flux affected the PVMR performance in the intermediate region and the membrane selectivity affected the performance in the equilibrium regime. Further, the limitations introduced by a low-flux membrane could be overcome by appropriate selection of the membrane area and that due to poor selectivity could be compensated to a certain extent by adjusting the feed ratio.
Keywords: comparison; Esterification; membrane reactor; performance; pervaporation membrane